The relationship between unprovoked venous thromboembolism, age, and acute myocardial infarction - SPENCER, F. A.; GINSBERG, J. S.; CHONG, A.; ALTER, D. A. (Journal of thrombosis and haemostasis, 2008)
Background: Patients with unprovoked venous thromboembolism (VTE) may be at increased risk of acute myocardial infarction (AMI). However, the nature and clinical significance of this association remain unclear, particularly as it relates to age of presentation. Methods: We performed a longitudinal matched cohort study utilizing multiple administrative databases. Ontario residents aged 20–64 years diagnosed with unprovoked VTE from 1 April 1991 to 31 March 1995 (n = 6065) were matched to a population cohort (n = 12 040) in 1 : 2 fashion on the basis of age, gender, socioeconomic class, cardiovascular risk factors and other comorbidities. The primary outcome was a comparison of relative risk of AMI over 10‐year follow‐up in subjects with unprovoked VTE (overall and stratified by age) vs. controls. Secondary outcomes included risk of death or the composite endpoint of AMI and/or death. Results: Patients 20–39 years of age presenting with unprovoked VTE had an increased risk of AMI [adjusted hazard ratio (HR) 3.92, 95% confidence interval (CI) 1.65–9.35] as compared to controls; the association was applicable to those without atherosclerotic risk factors at baseline. There was no significant relationship between unprovoked VTE and AMI among patients 40–64 years old, with or without atherosclerotic risk factors. Irrespective of age, patients with unprovoked VTE had an increased risk of all‐cause death or our composite endpoint of AMI and/or death as compared to patients without VTE. Conclusions: Unprovoked VTE is associated with a nearly 4‐fold higher risk of subsequent AMI among younger patient populations. Future studies must explore the risk–benefit tradeoffs of long‐term surveillance and management options among such patient populations.